Comparative performance and ecotoxicity assessment of Y2(CO3)3, ZnO/TiO2, and Fe3O4 nanoparticles for arsenic removal from water. Issue 8 (24th June 2022) - Salazar, H.; Martins, P. M.; Batista, Daniela; Shejale, K. P.; Sharma, R. K.; R., Krishnapriya; Ferdov, S.; Botelho, G.; Fidalgo-Marijuan, A.; Cássio, Fernanda; Lanceros-Mendez, S.
Abstract : This systematic study includes physical–chemical characterisation of nanomaterials, arsenic adsorption assays, adsorption mechanism proposal, and acute toxicity assays with Daphnia magna . Abstract : The application of nanomaterials to remove arsenic from water represents one of the most promising remediation methods nowadays. In this study, three active materials, Y2 (CO3 )3, ZnO/TiO2, and Fe3 O4, with different structural and morphological properties, were evaluated for their As(v ) adsorption capacity in contaminated water. Thus, the adsorption behaviour was assessed, including the influence of pH, adsorption kinetics, and isotherms. This work demonstrates that the active materials show a high adsorption performance, with adsorption efficiencies always close to 100%, leading to maximum adsorption capacities of 32.8, 37.3, and 35.8 mg g −1 for Y2 (CO3 )3, ZnO/TiO2, and Fe3 O4, respectively. The effects of suspended sorbent nanomaterials on Daphnia magna allowed us to estimate the lethal concentration that kills 50% of the test specimens (LC50 ) of 6.57 × 10 3 mg L −1, 28.7 mg L −1, and 1.91 × 10 6 mg L −1 for Fe3 O4, ZnO/TiO2 and Y2 (CO3 )3, respectively. Overall, this study confirmed the investigated materials' suitability for arsenic water remediation applications.